Sulfidation of magnetite with incorporated uranium. (August 2021) - Townsend, Luke T.; Morris, Katherine; Harrison, Robert; Schacherl, Bianca; Vitova, Tonya; Kovarik, Libor; Pearce, Carolyn I.; Mosselmans, J. Frederick W.; Shaw, Samuel
Abstract: Uranium (U) is a radionuclide of key environmental interest due its abundance by mass within radioactive waste and presence in contaminated land scenarios. Ubiquitously present iron (oxyhydr)oxide mineral phases, such as (nano)magnetite, have been identified as candidates for immobilisation of U via incorporation into the mineral structure. Studies of how biogeochemical processes, such as sulfidation from the presence of sulfate-reducing bacteria, may affect iron (oxyhydr)oxides and impact radionuclide mobility are important in order to underpin geological disposal of radioactive waste and manage radioactively contaminated land. Here, this study utilised a highly controlled abiotic method for sulfidation of U(V) incorporated into nanomagnetite to determine the fate and speciation of U. Upon sulfidation, transient release of U into solution occurred (∼8.6% total U) for up to 3 days, despite the highly reducing conditions. As the system evolved, lepidocrocite was observed to form over a period of days to weeks. After 10 months, XAS and geochemical data showed all U was partitioned to the solid phase, as both nanoparticulate uraninite (U(IV)O2 ) and a percentage of retained U(V). Further EXAFS analysis showed incorporation of the residual U(V) fraction into an iron (oxyhydr)oxide mineral phase, likely nanomagnetite or lepidocrocite. Overall, these results provide new insights into the stability of U(V) incorporated iron (oxyhydr)oxides during sulfidation, confirming the longer term retention of U in the solid phase under complex, environmentally relevant conditions. Graphical abstract: Image 1 Highlights: A highly controlled sulfidation of U(V) in nanomagnetite was performed. Small but significant fraction of U transiently liberated into solution over 3 days. U partitioned to solid phase after 10 months as a mixture of U(IV) and U(V) species.